The Effect of Fiscal Balance Funds on Local Economic Growth in Indonesia - Anggono, Priyo (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
The fiscal balance funds are the funds from the central government for the local government, and it has become the main revenue for the local governance. As the main revenue, the fiscal balance funds could affect the local economic growth. By looking at the data from the period of 2011 to 2018, this essay investigates two things, first is the relationship between fiscal balance funds and the local economic growth. This essay also identifies what are the major determinants of local economic growth in Indonesia is. Furthermore, do the results differ across regional groups. The essay finds that the relationship between fiscal balance funds have positive effect on economic growth. With the most significant funds are the DAU and DAK. The results also confirm that increasing human capital would increase economic growth. This essay also finds that even though the results for regions vary, capital expenditure still shows positive effect for economic growth. The findings from this essay would have important policy implication for the central government in Indonesia in reviewing the fiscal balance policy and determining the priority sectors